THE EVOLUTION OF IDEAS OF ANTHROPOLOGICAL OUTLOOK V. I. SHYNKARUK’S - Гушпит, Г. К. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article is dedicated to the problem of establishing of V.Shynkatuk’s anthropological ideas in Ukrainian philosophy. The author analyses an influence of I.Kant and G.Hegel of the formation of V.Shynkatuk’s human philosophy. It is researched the philosophy sense of categories of believe, hope and love by their evristic direction on the world and by their accordance to ideals.